Chapter 1 THE GOAL, RATIONALE, AND ORGANIZATION OF THE BOOK - Berger, Roni (Taylor & Francis, 2024)
Chapter 1: The idea that the struggle with traumatic events can generate, in addition to negative outcomes, also positive changes, flourishing, and growth has been reported throughout history around the globe and has gained visibility and support, specifically in the last decades. Research that documented growth following the struggle with highly stressful events mushroomed relative to diverse types of stressor events, in various socio-cultural contexts and during all developmental stages for individuals, couples, families, communities, and organizations. This chapter provides a review of the concept of posttraumatic growth (PTG), the model that delineates its process and critique relative to it. Research about the prevalence, characteristics, and correlates of PTG is reviewed, and clusters and gaps in the current knowledge are identified. The chapter further discusses the philosophy that informed the development of the book and the structure that emerged.